Seepage Property of Crushed Mudstone Rock in Collapse Column - Bo-Yang Zhang; Zhi-Bin Lin (Advances in Civil Engineering)
The karst collapse column composed of crushed rocks and fine argillaceous or clay particles is easy to form the fissure channels between the coal seam working face and the confined limestone aquifer under mining and causes water inrush disasters with the loss of underground water resource, economic losses, and casualties. It is of great necessity to understand the seepage properties of crushed rock in karst collapse column for the prevention of water inrush and the protection of underground water resource. A self-developed seepage test system is used in this paper to conduct laboratory experiments on seepage properties of crushed mudstone specimens. The effects of the particle size distribution, the porosity (specimen height), and the hydraulic pressure on the water flow velocity and the permeability of crushed specimen are analyzed. The results indicate that the permeability of specimen increases with the particle size, porosity, and hydraulic pressure. It can be known from the comparative experiments of progressive hydraulic pressure on one specimen and variable hydraulic pressure on different specimens with constant particle size and porosity that more fine particles leak out from the specimen with repeated application of hydraulic pressure on one specimen. Therefore, the permeability of one specimen is bigger than that of different specimens under the condition of same hydraulic pressure.